The effects of preoperative sugarless gum chewing on gastric fluid volume and pH - Siti Zubaidah MZ; Azlan Sani S; Muhammad M; Ooi, Joanna Su Min (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
There is a lack of consensus regarding the preoperative fasting period on gum chewing due to conflicting evidence. Our study aimed to determine the effects of preoperative sugarless gum chewing on gastric fluid volume and pH. This prospective randomised study was performed on patients who underwent elective operation under general anaesthesia. Sixty patients who fasted overnight were randomly assigned to either “non-chewing gum” as control or “chewing gum group” as intervention group who chewed one piece of gum upon the call to the operating theatre. They were further enquired whether gum chewing helped cope with hunger and reduced anxiety. Gastric volume and pH were determined immediately after induction of anaesthesia. Gum chewing had no significant effect on gastric fluid volume measured [30.4+13.6 (control) vs 29.1+11.6 ml (intervention), p = 0.693] and gastric fluid pH [1.4+0.4 (control) vs 1.6+0.4 (intervention), p = 0.05] while managing to reduce anxiety in 90.3% patients who chewed gum. Pre-operative gum-chewing did not increase in gastric fluid volume or a further reduction in gastric fluid acidity and was able to reduce anxiety in patients in the preoperative period.